TRACKING DEEP ANCIENT CRUSTAL COMPONENTS BY XENOCRYSTIC ZIRCONS OF PALEOZOIC FELSIC IGNEOUS ROCKS FROM THE ALTAI-EAST JUNGGAR TERRANE AND ADJACENT REGIONS AND ITS TECTONIC SIGNIFICANCE - Jianjun Zhang; Tao Wang; Ying Tong; Zhaochong Zhang; He Huang; Lei Zhang; Lei Guo; Peng Song; Zengqian Hou (Геодинамика и тектонофизика, 2017)
The deep crustal continental components and architecture of the Central Asian Orogenic Belt have long been a matter of debate [Wang et al., 2009; Kröner et al., 2014; Xiao et al., 2015; Yang et al., 2017]. We present an integrated study of geochronological and Hf-inzircon isotopic data for xenocrystic zircons from the Paleozoic granitoid rocks and associated felsic volcanic rocks of the Chinese Altai, East Junggar and nearby regions. The aim is to trace the age spatial distribution of deep old crustal components in these key parts of the western Central Asian Orogenic Belt.